Analisis Kesalahan Morfologi dalam Penulisan Caption dan Komentar di Salah Satu Postingan Akun Instagram @official.kpk - Ai Siti Nurjamilah; Fiqri Abdul Muqit; Khopipah Al Filani; Shofiyah Shofiyah; Muhammad Hanif Hukama (Universitas Palan, 2025)
The purpose of this study was to analyze language errors in the morphological category in captions and comments in one of the @official.kpk posts. The research method used is descriptive with a qualitative approach to describe the existence of errors or mistakes in writing captions and comments according to the procedures for analyzing language errors. The data source in this study is the @official.kpk Instagram post. on November 6, 2024. The data collection technique used was the purposive sampling technique to determine the data sample. Other data collection techniques used in this study were literature studies, documentation, and discourse analysis. The object data used was one post in the form of captions and comments. Data processing was carried out by collecting words that contained errors or mistakes, especially in the morphological category such as affixation or reduplication, then grouped. After grouping the data sources, the researcher conducted an analysis by analyzing using an analysis table and in accordance with applicable procedures. In the results and discussion section, it can be concluded that from one post that the researcher took, there were many errors and mistakes in the comments column, totaling 18 errors and mistakes.